VIDEO EDITING APPLICATION AS LEARNING MEDIA ON STUDENTS' CHARACTER EDUCATION IN MADRASAH TSANAWIYAH - Astri Wulandari (Universitas Tanjungpura, 2023)
In learning process activity, learning resources has an important role in achieving student learning outcomes. On the other hand, the lack of utilization is a problem for some educational institutions, especially at Madrasah Tsanawiyah. Mastery of technology for educators is not optimal and gives impact on student learning outcomes and less attractive. Students tend to learn with conventional methods and less motivated. To anticipate these problems, using technology-based learning resources is very appropriate at this time. The application of video editing-based technology can increase student motivation and educate students with creative characters. There are some video editing applications such as TikTok, Filmora, Kinemaster, CapCut and viva video as an alternative choice for students and educators to interact in the learning space. This study, was conducted to seven grade students at Madrasah Tsanawiyah Negeri 1 Kota Serang. It used qualitative methods and data obtained from the results of questionnaires, interview and observations. The results showed that the application of learning media through video editing applications was able to shape the character of students creative and innovated. From these result can be concluded that the video editing application is very helpful in the learning process as a learning media.